Consumer credit models : pricing, profit, and portfolios - Thomas, Lyn C. (Oxford ; New York : Oxford University Press, 2009)
The use of credit scoring, the quantitative and statistical techniques to assess the credit risks involved in lending to consumers has been one of the most successful if unsung applications of mathematics in business. Now with lenders changing their objectives from minimizing defaults to maximizing profits, the saturation of the consumer credit market allowing borrowers to more discriminating in their choice of which loans, mortgages and credit cards to use, among other reasons, this book reviews the current methodology and measures used in credit scoring and them looks at the models that can be used to address these new challenges.
Includes bibliographical references (p. [365]-369) and index.
nmn 15/05/13
Loans
Keywords: Consumer credit; Consumer credit models; Credit scoring systems